Challenges in teaching Psychological Assessment in Brazil: adapting actions - Lima, Thatiana Helena de; Cardoso, Hugo Ferrari [UNESP]; Schelini, Patrícia Waltz; Zanini, Daniela Sacramento (FapUNIFESP (SciELO), 2021)
The Covid-19 pandemic required many changes in several areas of Psychology, such as Psychological Assessment. The face to face teaching methods did not prove efficient in the remote modality and thus there was a need for a careful adaptation that would address techniques, such as psychological assessments, without impairing learning. Therefore, this study aimed to discuss training in psychological assessment, in light of the challenge resulting from the experience of the Covid-19 pandemic. Hence, we intend to offer subsidies for quality training in psychological assessment for the moment currently experienced
Desafíos en la Enseñanza de la Evaluación Psicológica en Brasil: adaptación de acciones
Desafios do Ensino da Avaliação Psicológica no Brasil: Adaptando Ações
Keywords: Covid-19; Psychological assessment; University education